Innovation in Public and Academic North American Libraries, in Words and Deeds - Rubin, Victoria L.; Gavin, Patrick T.; Kamal, Ahmad M. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Being innovative is a popular but ambiguous maxim in LIS. To elucidate how institutions use, and what they mean by the concept, we examine white literature and survey website features of 160 libraries across US and Canada. We identify patterns in the language and ethos of modern innovative librarianship. Être novateur est une maxime populaire bien qu’ambigüe en science de l’information. Pour mieux comprendre comment les institutions l’utilisent et quelle est la signification du concept, nous avons analysé les documents officiels et le contenu des sites Web de 160 bibliothèques aux États-Unis et au Canada. Sont identifiés des modèles d’utilisation langagière et l’ethos de la bibliothéconomie moderne novatrice. ***Full paper in the Canadian Journal of Information and Library Science***